2010
DOI: 10.15283/ijsc.2010.3.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant Human Erythropoietin On the Stemness of Bone Marrow-derived Mesenchymal Stem Cells in vitro

Abstract: The purpose of this study was to investigate the effects of the recombinant human erythropoietin (rhEPO) on proliferative and multi-differentiation potential of the bone marrow-derived mesenchymal stem cells (MSCs). The MSCs were isolated primarily from bone marrow of adult rat and purified at increasing passage. A purified population of MSCs can be obtained about 2 weeks after the initiation of culture. After three passages (P3-MSCs), bone marrow-derived adherent cells were identified, then different concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 22 publications
(35 reference statements)
0
23
0
Order By: Relevance
“…Endogenous erythropoietin and recombinant erythropoietin are identical, except for some minor differences in glycosylation (Koury andBondurant 1992, Rölfing 2014). Human recombinant erythropoietin was first characterised as a hematopoietic factor (Ye et al 2010). It was shown that this substance stimulated differentiation and proliferation of erythroid precursor cells (Broudy et al 1991, Ye et al 2010.…”
Section: Recombinant Erythropoietin (Epoetin)mentioning
confidence: 99%
See 3 more Smart Citations
“…Endogenous erythropoietin and recombinant erythropoietin are identical, except for some minor differences in glycosylation (Koury andBondurant 1992, Rölfing 2014). Human recombinant erythropoietin was first characterised as a hematopoietic factor (Ye et al 2010). It was shown that this substance stimulated differentiation and proliferation of erythroid precursor cells (Broudy et al 1991, Ye et al 2010.…”
Section: Recombinant Erythropoietin (Epoetin)mentioning
confidence: 99%
“…Human recombinant erythropoietin was first characterised as a hematopoietic factor (Ye et al 2010). It was shown that this substance stimulated differentiation and proliferation of erythroid precursor cells (Broudy et al 1991, Ye et al 2010. Recombinant forms of erythropoietin are epoetin-alfa (human erythropoietin which is produced in cell culture using recombinant DNA technology), epoetin-beta (which is a synthetic recombinant form of EPO) and long-term acting analogue darbepoetin-alfa (which is also a synthetic form of erythropoietin) (Arcasoy 2008, Uversky andRedwan 2017).…”
Section: Recombinant Erythropoietin (Epoetin)mentioning
confidence: 99%
See 2 more Smart Citations
“…The recombinant human erythropoietin (rhEPO) can not only keep features of stem cells but also preserve its multi-lineage differentiation ability after suitable EPO treatment. But extra investigation on the involved mechanism can lead to a better understanding between EPO and MSC stemness maintenance (Ye et al 2010).…”
Section: Both Intrinsic and Extrinsic Parametersmentioning
confidence: 99%